Sudden peak in tetrodotoxin in French oysters during the summer of 2021: Source investigation using microscopy, metabarcoding and droplet digital PCR - Biessy, Laura; Pearman, John K.; Mertens, Kenneth; Réveillon, Damien; Savar, Veronique; Hess, Philipp; Hampton, Hannah; Thompson, Lucy; Lebrun, Luc; Terre-terrillon, Aouregan; Smith, Kirsty F. (Toxicon, 2024)
Tetrodotoxin (TTX) is a potent neurotoxin causing human intoxications from contaminated seafood worldwide and is of emerging concern in Europe. Shellfish have been shown to contain varying TTX concentrations globally, with concentrations typically higher in Pacific oysters Crassostrea gigas in Europe. Despite many decades of research, the source of TTX remains unknown, with bacterial or algal origins having been suggested. The aim of this study was to identify potential source organisms causing TTX contamination in Pacific oysters in French coastal waters, using three different techniques. Oysters were deployed in cages from April to September 2021 in an estuary where TTX was previously detected. Microscopic analyses of water samples were used to investigate potential microalgal blooms present prior or during the peak in TTX. Differences in the bacterial communities from oyster digestive glands (DG) and remaining flesh were explored using metabarcoding, and lastly, droplet digital PCR assays were developed to investigate the presence of Cephalothrix sp., one European TTX-bearing species in the DG of toxic C. gigas. Oysters analysed by liquid chromatography-tandem mass spectrometry contained quantifiable levels of TTX over a three-week period (24 June–15 July 2021), with concentrations decreasing in the DG from 424 μg/kg for the first detection to 101 μg/kg (equivalent to 74 to 17 μg/kg of total flesh), and trace levels being detected until August 13, 2021. These concentrations are the first report of the European TTX guidance levels being exceeded in French shellfish. Microscopy revealed that some microalgae bloomed during the TTX peak, (e.g., Chaetoceros spp., reaching 40,000 cells/L). Prokaryotic metabarcoding showed increases in abundance of Rubritaleaceae (genus Persicirhabdus) and Neolyngbya, before and during the TTX peak. Both phyla have previously been described as possible TTX-producers and should be investigated further. Droplet digital PCR analyses were negative for the targeted TTX-bearing genus ...